Estudio de factibilidad para la creación de una empresa productora y comercializadora de mermelada de membrillo en la ciudad de Loja - Guayanay Correa, Fredy Ramiro (2018)
The present research work refers to the "STUDY OF FEASIBILITY FOR THE CREATION OF A COMPANY PRODUCER AND MARKETER OF QUINCE JAM IN THE CITY OF LOJA". Its process begins based on the problems analyzed in the project, fulfilling the main objective of conducting a feasibility study for the creation of a company, producer and marketer of quince jam in the city of Loja. To determine the feasibility of the project, the specific objectives were raised, which involve the elements of the investment project such as: Market study; Technical study; Administrative study; Financial study and financial evaluation. In the Market Study it was determined that there is an unsatisfied demand for the first year of 634,758 pieces of marmalade of 300gr, therefore, within the technical study the company in the city of Loja will develop its activities with an installed capacity of 327,600 units of 300gr per year and a used capacity of 78,000 units for the five years of the project taking into account that the machinery will operate at 100% capacity. In the administrative-organizational study, it was determined that the company will have 4 hierarchical levels: Executive, Advisor, Assistant, and Operative, also requires hiring 6 people, creating equal number of work sources. The company will be constituted under the legal form of Unipersonal Limited Liability Company, its registered name is "MELELADAS ANGELITA EURL."; Its term will be 5 years. Within the analysis of the Financial Study the investments in fixed assets, deferred and working capital required by the project were determined, establishing that for the operation of the company in the first year, $ 28,562.53 must be invested; of this total, 65% is the contribution of own capital and the remaining 35% will be obtained through a loan at Banco de Loja with an annual interest rate of 16.06%. The total cost for the first year of production is $ 102,864.01, with a production of 78,000 units, the unit cost is $ 1.32, to which is added 30% of profit reaching an adjusted sale price at public of $ 1.70. According 5 to the estimations made, the company will have a net profit of $ 17,061.02 for the first year of useful life, and the cash flow shows that, in this same period, the company will have a net flow of $ 20,406.13. After having carried out the Financial Evaluation, with its respective indicators, the project has a Net Present Value of $ 38,315.09 dollars, therefore it fulfills the objective of maximizing the investment; likewise with an Internal Rate of Return of 41.96%, higher than the TMAR (18.36%); The Benefit / Cost Ratio shows that for each dollar invested, the company will generate $ 0.29 ctvs. of profit; within the Capital Recovery Period, the capital invested is recovered in 1 year, 9 months, 3 days, obtaining as result positive indicators, which assure that this project can be carried out without major difficulties. Finally, in the Sensitivity Analysis, it is shown that the project supports an increase in its costs of up to 17.84% and a decrease in its income of up to 13.87%. Consequently, thanks to the results obtained, it is concluded that the project is feasible technically, organizationally, legally, financially and economically. Determining the feasibility of the project The respective recommendations were also issued, which would provide many benefits in putting them into practice; then reference is made to the bibliography used in the research process, the instruments used in the process are appended and, finally, the index that allows a quick overview of the content of this work is outlined